Proposing a suitable soil quality index for natural, secondary and rehabilitated tropical forests in Malaysia - Abdu, Arifin; Karam Singh, Daljit Singh; Jusop, Shamshuddin; Nik Ab. Majid, Nik Muhamad; Othman, Radziah; Abdul Hamid, Hazandy; I., Zahari (Academic Journals, 2012)
There are numerous types and categories of soil indices developed for soil fertility and quality evaluation. However, there is still lacking in suitable indices for quantifying the fertility of degraded and rehabilitated forests in the tropics. The objective of this present study was to develop a suitable soil index from the existence soil indices which were suitable for natural, secondary and rehabilitated tropical forest soil known as Tropical Soil Quality Index (TSQI). This study was carried out at Chikus lowland dipterocarp (natural forest and planted S. leprosula plots) and Tapah Hill (enrichment planting and secondary forest plots) Forest Reserves, Perak. Soil samples were collected at 0 to 15 cm and 15 to 30 cm depth with six subplots (20 × 20 m) for each plot. Selected soil parameters include bulk density, coarse fragment, soil acidity, total carbon, total nitrogen, exchangeable magnesium, exchangeable potassium, exchangeable calcium, available phosphorus, sodium saturation, aluminium saturation, and microbial biomass. The proposed Tropical Soil Quality Index (TSQI) incorporates all important properties of soils mainly physical, chemical and biological which are able to give adequate information on the soil fertility status. Results presented in this proposed index were based on the score accumulated from parameters that have been analyzed. This index is suitable to be used for the evaluation of current fertility status of tropical soils by which the techniques used for soil analyses were based on the acidic nature of most soils in the tropics, including Malaysia. From the proposed TSQI, enrichment planting has the same level of 59.09% TSQI with natural forest which prove that rehabilitation of degraded forest land with mix tree after 42 years of planting is similar with undisturbed natural forest. In conclusion, the proposed TSQI incorporates selected soil physical, chemical and biological properties which are crucial for soil fertility evaluation of degraded forest land and this index will helps soil fertility evaluator to study and describe the current fertility status of degraded forest land soil especially for tropical regions.